5(-2m)+4=89

Simple and best practice solution for 5(-2m)+4=89 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(-2m)+4=89 equation:


Simplifying
5(-2m) + 4 = 89

Remove parenthesis around (-2m)
5 * -2m + 4 = 89

Multiply 5 * -2
-10m + 4 = 89

Reorder the terms:
4 + -10m = 89

Solving
4 + -10m = 89

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '-4' to each side of the equation.
4 + -4 + -10m = 89 + -4

Combine like terms: 4 + -4 = 0
0 + -10m = 89 + -4
-10m = 89 + -4

Combine like terms: 89 + -4 = 85
-10m = 85

Divide each side by '-10'.
m = -8.5

Simplifying
m = -8.5

See similar equations:

| 2b+5p=5.2 | | 3(x-4)+68=-4 | | -r+1=-7+4r-r | | 2(3x-13)=-20 | | 3(c+2+1)=9c+3 | | 86=5x-14 | | y+6-4y-3=-30 | | 1-n=13-4n | | -5(x+3)(x+8)= | | 9x^2-18w+24=0 | | 30c=18360 | | 2(1-16a)=-2a-6(a-7) | | 6x+11=8x+13 | | 3k-7k=-9-k | | 27=2y-13 | | -(-9-6x-6y)= | | 980+n=1020 | | E=(8) | | -5=3x+8 | | -4x+8=-12+x-8-7 | | -(4x-10)+2(3x+15)= | | 4x^3+24x^2+12x-40=0 | | 6x-3y+14w-5y-4w+9x= | | 592=2L+2(5L+6) | | 2(-1)+9= | | 12x+9=9x-18 | | 4x-5=3-7x | | 48=4(x+10) | | 4u^2-4=15 | | 5v+7=6v-11 | | 6x=5x+16 | | 16(x+3)-4x=4(3x+2)-12 |

Equations solver categories